Yields of sorghum and millet and stover consumption by livestock in the subhumid zone of Nigeria - Powell, J.M. (1985)
Describes a study to determine grain & stover yields of sorghum & millet under traditional farming systems in the subhumid zone of Nigeria and observe consumption of stover components by livestock within the first two months of the dry season, w. data on chemical composition of leaf & stalk components.